A-107 How Important Is the Lymphoid Tissue Reservoir?. (March 2017) - Schacker, Timothy
Abstract : Progress towards a cure for HIV infection is hampered by limited understanding of the size, location, and dynamic nature of virus reservoirs, especially the latent reservoir. We have used several in situ hybridization and immunohistochemistry techniques to directly assess the location and frequency of SIV and HIV RNA and DNA positive cells. Our previous studies document the size of these reservoirs, especially in lymphatic tissues however those data were collected in an era when ART was less effective than current regimens. In this talk I will review these data and provide new information on the size and location of virus reservoirs in the modern ART era using modern in situ technologies. I will discuss data from non-human primate studies where more complete tissue analysis can be accomplished from every organ system as well as longitudinal data from HIV infected people before and during ART. These data are especially relevant as we contemplate various strategies to purge these reservoirs in an effort to cure the infection.